PREDICTION OF ROTARY ACCURACY OF FRAME-TYPE COMBINED SPINDLE BASED ON FORM AND POSITION ERRORS - NI WeiHua; JIANG XiaoHui (Jixie qiangdu)
Frame-type combined spindles are widely used in precision products such as CNC rotary tables and aerospace flight simulators. Due to the multiple geometric errors in their component parts,the rotary precision of the frame-type combined spindle is directly affected,which further affected the accuracy of the whole axis. In this paper,by correcting the small displacement torsor expression of the cylindrical pair,the three-dimensional cylindricity tolerance was integrated into the Jacobian torsor tolerance analysis model of the frame-type combined spindle. It made up for the deficiency that the Jacob torsor model could not deal with the form tolerance. On this basis,the rotary datum of the frame-type combined spindle was modeled and characterized. The coaxiality error of the two working shaft segments in the frame-type combined spindle was solved,and the limiting rotary precision of the frame-type combined spindle under the influence of the multinomial form and position errors was predicted. The measurement results proved the correction of the method.